ARISTOTLE AS CRITIC OF PLATO’S RHETORIC? Some conclusions, questions and implications - Bloomquist, Gregory (Science et Esprit, 2020)
Plato is often understood to be merely an outspoken critic of rhetoric and Aristotle a systematizer of rhetoric. The reality is more complex. Plato’s criticism is not of rhetoric per se but of a particular (Sophistic) kind of rhetoric; his work actually evidences a keen desire to enshrine a true rhetoric, one that will enable instruction in truth to happen. Nor is Aristotle a critic of Plato; rather, Aristotle provides a systematic approach to political discourse and human language as it is in practice. Aristotle thus establishes both the foundations for analysis of democratic political discourse and the analytical groundwork for the much later analysis of “ordinary language.”